KINERJA INSPEKTORAT DAERAH PROVINSI SULAWESI TENGAH - Basiro, Djawaria (Katalogis, 2015)
This study aims to identify and analyze the performance of the Regional Inspectorate of Central Sulawesi Province. This type of research uses descriptive qualitative approach, to measure performance based on the theory of Schermerhorn, Jr. (1994) in Dwiyanto and Baveola (2001: 3), consisting of: inputs (inputs), outputs (outputs), and outcomes (results). The collection of data through observation, interview, and documentation, dianlisis through the stages of data reduction, data display, and conclusion. The research concludes that, there was an imbalance of the amount of control object (SKPD) and the space scope of the task with the availability of auditors. Extension of the scope of duties and responsibilities of supervision, not offset by the availability of resources auditor apparatus, the availability of an adequate budget, the lack of knowledge, skills, and competence of auditors in the field of supervision, due to a lack of education and training intensity, so that the outputs and outcomes produced less efficiently and effective both in quantity and quality. The ability of the organization to be not optimal resources to improve the quality of supervision, monitoring the regional administration which encourage corruption eradication practices, and especially in realizing the performance accountability of local government, in order to create governance Good governance and clean government.